MENTORING FOR STRENGTHENING THE RELIGIOUS UNDERSTANDING OF YOUTH AT NURUL YAQIN MOSQUE, PESISIR BARAT DHARMA CAMPLONG - Ismail, Ismail (Ngejha, 2025)
This article discusses the mentorship of mosque youth in strengthening their religious understanding. The focus of this activity is on the youth of Nurul Yaqin Mosque, located in Pesisir Barat Hamlet, Dharma Camplong Village, Camplong District, Sampang Regency, who exhibit weaknesses in understanding religious values. This program aims to enhance their religious comprehension, mastery of tajwid (Qur'anic recitation rules), and to develop Islamic moral character through tahsin study sessions. Over two months, the mentoring program was conducted in four stages: introduction to the Qur'an and the virtues of recitation, introduction to tajwid science, understanding Islamic worship practices, and the development of Islamic character. The outcomes of this community service program show that the youth experienced improvements in religious knowledge and demonstrated growth in Islamic character traits such as empathy, honesty, patience, and social care. Although some challenges were encountered, the majority of the youth consistently participated. This program highlights the importance of empowering youth to address weaknesses in religious understanding. A strong grasp of religious values helps adolescents face daily challenges and builds strong character. Furthermore, the tahsin study program shows that involving parents in activities can increase youth support and participation.